The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3748/wjg.v22.i23.5406
|View full text |Cite
|
Sign up to set email alerts
|

Association of HER2 status with prognosis in gastric cancer patients undergoing R0 resection: A large-scale multicenter study in China

Abstract: The positive status of HER2 based on IHC staining was not related to the survival in patients with GC among the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
1
18
2
2
Order By: Relevance
“…In other studies, HER2 overexpression was defined as HER2 3+ in IHC and as HER2 2+ in IHC and specimens with amplified HER chromosome levels based on fluorescence in situ hybridization (FISH) or silver-enhanced in situ hybridization (SISH). HER2 overexpression rates ranged from 6 to 35% [8–12, 1518, 20, 22, 28, 29]. IHC and FISH/SISH showed a concordance rate of HER2 expression to be 88.5–93.5% [11, 18, 25, 30, 31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, HER2 overexpression was defined as HER2 3+ in IHC and as HER2 2+ in IHC and specimens with amplified HER chromosome levels based on fluorescence in situ hybridization (FISH) or silver-enhanced in situ hybridization (SISH). HER2 overexpression rates ranged from 6 to 35% [8–12, 1518, 20, 22, 28, 29]. IHC and FISH/SISH showed a concordance rate of HER2 expression to be 88.5–93.5% [11, 18, 25, 30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…HER2 overexpression rates ranged from 6 to 35% [8–12, 1518, 20, 22, 28, 29]. IHC and FISH/SISH showed a concordance rate of HER2 expression to be 88.5–93.5% [11, 18, 25, 30, 31]. The rates of specimens with HER2 2+ in IHC and amplified HER2 gene levels based on FISH (or SISH) were 4% [11], 7.7% [8], and 20% [9], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients with HER2 (+) gastric cancer showed an improved outcome with chemotherapy. The association of HER2 status with prognosis in a total of 1562 gastric cancer patients undergoing R0 resection was also investigated by Shen et al [17] They reported that there were no significant associations between HER2 status and DFS or OS in multivariate analysis. In our study, the incidence of HER2 positivity was 16%.…”
Section: Local Recurrences and Distant Metastasismentioning
confidence: 99%
“…In China, according to cancer statistics, the estimated incidence rate for GC was 679.1 per 100,000 people per year, and the mortality rate was ~498.0 per 100,000 people per year, while over 60% patients were in the advanced stage (2). Since the prognosis for GC patients is very poor, many molecular markers, including HER2, E-cadherin, EGFR, and KRAS have been evaluated as candidate prognostic factors for GC (3,4).…”
Section: Introductionmentioning
confidence: 99%